2019
DOI: 10.15252/emmm.201910293
|View full text |Cite
|
Sign up to set email alerts
|

Functional systemic CD 4 immunity is required for clinical responses to PD ‐L1/ PD ‐1 blockade therapy

Abstract: The majority of lung cancer patients progressing from conventional therapies are refractory to PD ‐L1/ PD ‐1 blockade monotherapy. Here, we show that baseline systemic CD 4 immunity is a differential factor for clinical responses. Patients with functional systemic CD 4 T cells included all objective responders and could be identified before the start of therapy by having a high proportion of memory CD … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(155 citation statements)
references
References 46 publications
10
137
0
2
Order By: Relevance
“…Despite known associations between pre-treatment TME characteristics and response [see references (15) and (16) for comprehensive reviews of predictive biomarkers], strategies to induce a responsive phenotype and thus sensitize cancers to ICB are only beginning to be developed. Systemic immunity and the local immune response at the effector site are obviously linked, and indeed several studies, both in animal models and patients, have shown that a degree of systemic immunity is required for tumors to respond to ICB (17,18). Here, we focus on factors within the TME: we summarize and contextualize recent studies characterizing the features of an ICB responsive, contrasting with a non-responsive, TME (Figure 1), and discuss selected therapeutic interventions designed to modulate that environment toward a responsive phenotype (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Despite known associations between pre-treatment TME characteristics and response [see references (15) and (16) for comprehensive reviews of predictive biomarkers], strategies to induce a responsive phenotype and thus sensitize cancers to ICB are only beginning to be developed. Systemic immunity and the local immune response at the effector site are obviously linked, and indeed several studies, both in animal models and patients, have shown that a degree of systemic immunity is required for tumors to respond to ICB (17,18). Here, we focus on factors within the TME: we summarize and contextualize recent studies characterizing the features of an ICB responsive, contrasting with a non-responsive, TME (Figure 1), and discuss selected therapeutic interventions designed to modulate that environment toward a responsive phenotype (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1 is overexpressed in many tumor types to evade the immune attack and its expression generally (but not always) correlates with progression (Gato-Canas et al, 2017;Escors et al, 2018;Bocanegra et al, 2019;Kattan et al, 2019). PD-1 is expressed in T lymphocytes and interferes with their activation when bound with their ligands PD-L1, inhibiting the effector phase and thus dampening the ability of these T cells to kill cancer cells (Keir et al, 2008;Gato-Canas et al, 2017;Zuazo et al, 2019).…”
Section: Pd-1/pdl-1 Clinical Trialsmentioning
confidence: 99%
“…Recent studies demonstrate that ICI therapies do also alter the dynamics and characteristics of systemic immune cell populations. Interestingly, some of these studies highlight the CD28-CD80 costimulation signaling pathway as a major contributor to efficacious responses to ICI (Hui et al, 2017;Zuazo et al, 2019). Indeed, several studies show a key role for IL-12-expressing dendritic cells with cross-presentation capacities for good responses to immunotherapies (Kerkar et al, 2011;Goyvaerts et al, 2015;Berraondo et al, 2018;Garris et al, 2018;Etxeberria et al, 2019).…”
Section: Tumor-extrinsic Factors and Resistance To Pd-l1/pd-1 Blockadmentioning
confidence: 99%
“…We have been interested for several years in PD-L1/PD-1 signaling mechanisms in the context of antitumor immunity. We carried out a recent translational project quantifying the relative percentages in peripheral blood of CD4 and CD8 T cell differentiation subsets in NSCLC patients treated with anti-PD-1/PD-L1 immunotherapies [33]. T cells can be classified according to CD27 and CD28 expression profiles into poorly differentiated (CD27 + CD28 + ), intermediately differentiated (CD27 -CD28 + ), and highly differentiated (CD27 -CD28 -) subsets.…”
Section: Cd4 T Cellsmentioning
confidence: 99%
“…In NSCLC patients under anti-PD-1/anti-PD-L1 immunotherapy that we have analyzed, most non-responders had T cells that simultaneous co-expressed PD-1 and LAG-3. Indeed, co-blockade with a combination of anti-PD-1 and anti-LAG-3 antibodies was sufficient to increase T cell activation from non-responder patients [33]. Fine mapping of the expression profiles of immune checkpoints in peripheral T cells could be indicative of the particular inhibitor combination to be used in these patients, especially when a plethora of other ICI are currently under study in different clinical trials.…”
Section: Future Perspectivesmentioning
confidence: 99%